Afghanistan transport sector master plan update (2017-2036). (Metro Manila, Philippines Asian Development Bank, 2017)
It provides a program of prioritized investments, and recommends urgent capacity building measures. As transportation in Afghanistan is central to social stability and peace building efforts, the development results generated by the master plan will extend beyond the boundaries of the transport sector.
Keywords: Transportation and the state -- Afghanistan; Electronic books